National Study of School Psychologists' Use of Evidence-Based Assessment in Autism Spectrum Disorder. Issue 1 (2nd January 2017) - Aiello, Rachel; Ruble, Lisa; Esler, Amy
ABSTRACT: This study aimed to better understand predictors of evidence-based assessment practices for autism spectrum disorder (ASD). Nationwide, 402 school psychologists were surveyed for their knowledge of and training and experience with ASD on assessment practices, including reported areas of training needs. The majority of school psychologists reported that they did not engage in comprehensive assessment of ASD, which was defined as assessments that consider all areas of development in addition to the use of ASD-specific instruments. Results from logistic regression revealed that experience and training, working with young children with ASD, and geographic location predicted use of evidence-based assessment practices. Experience and training with ASD was the strongest predictor of evidence-based assessment. No differences in training needs were indicated by school psychologists whose practices were consistent with evidence-based assessment and those whose practices were not. Overall, the results identified gaps between best and current practices by school psychologists and highlight areas of need for additional training and professional development.